Deposition of intrinsic hydrogenated amorphous silicon for thin‐film solar cells – a comparative study for layers grown statically by RF‐PECVD and dynamically by VHF‐PECVD. (31st July 2012) - Zimmermann, T.; Flikweert, A. J.; Merdzhanova, T.; Woerdenweber, J.; Gordijn, A.; Rau, U.; Stahr, F.; Dybek, K.; Bartha, J. W.
ABSTRACT Hydrogenated amorphous silicon (a‐Si:H) is conventionally deposited using static plasma‐enhanced chemical vapor deposition (PECVD) processes. In this work, a very high frequency (VHF) dynamic deposition technique is presented, on the basis of linear plasma sources. This configuration deploys a simple reactor design and enables continuous deposition processes, leading to a high throughput. Hence, this technique may facilitate the use of flexible substrates. As a result, the production costs of thin‐film silicon solar cells could be reduced significantly. We found a suitable regime for the homogeneous deposition of a‐Si:H layers for growth rates from 0.35–1.1 nm/s. The single layer properties as well as the performance of corresponding a‐Si:H solar cells are investigated and compared with a state‐of‐the‐art radio frequency (RF) PECVD regime. By analyzing the Fourier transform infrared spectroscopy spectra of single layers, we found an increasing hydrogen concentration with deposition rate for both techniques, which is in agreement with earlier findings. At a given growth rate, the hydrogen concentration was at the same level for intrinsic layers deposited by RF‐PECVD and VHF‐PECVD. The initial efficiency of the corresponding p–i–n solar cells ranged from 9.6% at a deposition rate of 0.2 nm/s (RF regime) to 8.9% at 1.1 nm/s (VHF regime). After degradation, the solar cell efficiency stabilized between 7.8% and 5.9%, respectively. The solar cells incorporating intrinsic layers grown dynamically using the linear plasma sources and very high frequencies showed a higher stabilized efficiency and lower degradation loss than solar cells with intrinsic layers grown statically by RF‐PECVD at the same deposition rate. Copyright © 2012 John Wiley & Sons, Ltd.